Dangdut Songs as Soundtracks for Content on TikTok - Pattiruhu, Misael Juda Alexander; Suharto, Suharto (Jurnal Seni Musik, 2024)
This study aims to investigate how dangdut songs are used as background music for content on the TikTok application. This study employed descriptive qualitative method to examine the popularity of five selected dangdut koplo songs among its content creators. Data collection techniques involved direct documentation of available data within the application. The findings indicate that TikTok plays a significant role in shaping trends in content types and popularizing songs used as background music. Songs such as "Ngopi Maszeh," "Rungkad," "Mendung Tanpo Udan," "Ojo Dibandingke," and "Los Dol" are frequently chosen by TikTok content creators as background music. The choice of content types by creators is influenced by the stimulating or calming musical elements in the selected songs. Thus, TikTok not only serves as an entertaining social platform but also stands as a major force in influencing cultural trends and supporting the global music industry through innovative and inspirational means